2006
DOI: 10.3892/ijmm.17.6.1077
|View full text |Cite
|
Sign up to set email alerts
|

Creatine supplementation increases soleus muscle creatine content and lowers the insulinogenic index in an animal model of inherited type 2 diabetes

Abstract: Creatine supplementation may exert beneficial effects on muscle performance and facilitate peripheral glucose disposal in both rats and human subjects. The present study was undertaken to explore the effects of creatine supplementation on the ATP, creatine, phosphocreatine and glycogen content of white and red gastrocnemius and soleus muscles and on blood D-glucose and plasma insulin concentrations before and during an intravenous glucose tolerance test in Goto-Kakizaki rats, a current animal model of inherite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
1
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 29 publications
1
26
1
3
Order By: Relevance
“…In a diabetes experimental model, it has been observed that creatine supplementation can improve the sensibility to insulin in extrapancreatic sites (25) . Other works which study the relationship between creatine use and glucose metabolism show that such supplementation, besides the expected benefits in the application in sports medicine, could have other applications.…”
Section: Discussionmentioning
confidence: 99%
“…In a diabetes experimental model, it has been observed that creatine supplementation can improve the sensibility to insulin in extrapancreatic sites (25) . Other works which study the relationship between creatine use and glucose metabolism show that such supplementation, besides the expected benefits in the application in sports medicine, could have other applications.…”
Section: Discussionmentioning
confidence: 99%
“…Essa possibilidade parece ser bastante plausível, já que alguns grupos, incluindo o nosso, demonstraram o efeito sinérgico da creatina ao exercício na captação de glicose (3,6,21) . Em suma, a suplementação de creatina não influenciou a captação periférica de glicose e os estoques de glicogênio muscular e hepático em ratos submetidos à atividade física por quatro e oito semanas.…”
Section: Discussionunclassified
“…Only Ferrante et al (2000) studied mice; the other studies used rats (Rooney et al 2002;Young and Young 2002;Ju et al 2005;Souza et al 2006;Op't Eijnde et al 2006;Freire et al 2008;Vaisy et al 2011;Eijnde et al 2001;Nicastro et al 2012;Araújo et al 2013). Eight studies investigated healthy animals (Young and Young 2002;Rooney et al 2002;Ju et al 2005;Souza et al 2006;Freire et al 2008;Eijnde et al 2001;Vaisy et al 2011;Araújo et al 2013), Ferrante et al (2000 used a transgenic mouse model of Huntington's Disease, Op't Eijnde et al (2006) studied Goto-Kakizaki rats (a animal model of inherited T2DM), and Nicastro et al (2012) used rats treated with dexamethasone. Four studies examined the effects of creatine supplementation associated with exercise training on glucose metabolism (Souza et al 2006;Freire et al 2008;Vaisy et al 2011;Araújo et al 2013), and seven studies The search strategy consists of two separate components and each component consists of the key words related to "creatine supplementation" and the key words related to "glucose metabolism" individually.…”
Section: Animal Studiesmentioning
confidence: 96%
“…One study did not mention the sample size . Six studies were controlled (Ferrante et al 2000;Eijnde et al 2001;Ju et al 2005;Souza et al 2006;Op't Eijnde et al 2006;Araújo et al 2013), and 5 were randomized and controlled (Young and Young 2002;Rooney et al 2002;Freire et al 2008;Vaisy et al 2011;Nicastro et al 2012). The median sample size was 63 animals (ranging from 8 to 72).…”
Section: Animal Studiesmentioning
confidence: 98%
See 1 more Smart Citation